Peran Orang Tua dalam Meningkatkan Pelaksanaan Magrib Mengaji di Masjid Al-Falah Desa Suka Maju Kecamatan Tambusai - Sarmadhan Lubis (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
Magrib Mengaji is one of the religious habituation programs aimed at instilling Islamic values in children from an early age, particularly in reading and understanding the Qur'an. The implementation of this activity is not solely dependent on the mosque or the Qur'an teachers, but is also greatly influenced by the active role of parents. Parents play a crucial role in shaping habits, providing motivation, and guiding their children to regularly participate in religious activities. This study aims to explore and describe the role of parents in enhancing the implementation of Magrib Mengaji at Al-Falah Mosque, Sukamaju Village, Tambusai District. The Magrib Mengaji program is designed to build children's character and morals through the habit of reading the Qur'an after the Maghrib prayer. Parents act as motivators, companions, and supervisors in supporting their children's participation in this activity. This research employs a qualitative approach with descriptive methods. Data collection techniques include observation, interviews, and documentation. The research subjects are parents of children who participate in Magrib Mengaji, the Qur'an teachers, and the children themselves. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The findings indicate that parents actively motivate, guide, and create a supportive home environment to encourage their children to consistently attend Magrib Mengaji. Supporting factors include family involvement, a religious environment, and the role of Qur'an teachers. Meanwhile, inhibiting factors include parents' busy schedules, decreased interest from children, fatigue after school, and distractions from electronic devices. With consistent parental involvement, the implementation of Magrib Mengaji can be more optimal and sustainable.